Novel near-infrared emission from crystal defects in MoS2 multilayer flakes - F. Fabbri (Nature Portfolio, 2016)
Impurities and vacancies are commonly found within the crystalline lattice of transition metal dichalcogenides, however they are usually seen as detrimental for their optical properties. Here, the authors demonstrate that sulfur vacancies in MoS2can give rise to a near-infrared emission peak.